Konsep Manusia Ideal dalam Prespektif Friedrich Nietzsche dan Syed M Naquib Al-Attas - Randi Rizananta; Alwan Abidin; Dzatu Aliviatin Nuha (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
This study discusses the comparison between the concept of the ideal human in Friedrich Nietzsche's thinking with the idea of Übermensch and Syed Muhammad Naquib al-Attas with the concept of Insān Kullī. This research is important because it delves into the ontological foundations that shape the direction and values in the formation of the ideal human being, which directly impacts the direction of civilization. The purpose of this research is to analysis the basic characteristics of each concept and to reveal the fundamental differences in Western and Islamic worldviews. This research uses a qualitative approach with a literature review and descriptive analysis method. The results of this research show that Übermensch is an individual who rejects transcendent values and builds an autonomous existence through the will to power, while Insān Kullī is a civilised figure who submits to revelation and balances reason and spirituality. The novelty of this research lies in its comprehensive comparative approach between two contrasting philosophical paradigms. Its implications are that understanding the ideal human being within the framework of each metaphysics is crucial in determining the direction of education, social development, and civilisational identity. These findings are also relevant as a conceptual foundation for the development of education and character building based on spiritual and intellectual values.